Ureteric Injury During Hysterectomy: A Case Report - Nura Ulfa; Trika Irianta; M. Hamsah; Nasrudin A.M.; Masita Fujiko; Mona Nulanda (Newinera Publisher, 2025)
Ureteral trauma is an uncommon but serious iatrogenic complication of hysterectomy, with risk influenced by surgical indication, patient factors, and intraoperative conditions. A 50-year-old woman presented with oliguria six days after hysterectomy for uterine myoma. She had abdominal distension and mild tenderness, with laboratory findings showing impaired renal function. Ultrasonography revealed bilateral hydroureteronephrosis and intraperitoneal ascites. Emergency exploratory laparotomy identified approximately 1.5 liters of intraperitoneal urine, bilateral ureteral dilatation, and bilateral distal ureteral ligation with urine leakage. Surgical management included intraperitoneal drainage, bilateral ureteroneocystostomy, ureteral stenting, peritoneal lavage, and bladder drainage. Eight days later, the patient developed abdominal wound dehiscence and underwent bilateral ureterocutaneostomy in collaboration with a urology surgeon. At follow-up, the patient showed gradual improvement and was able to resume daily activities under regular outpatient monitoring. Management of ureteral trauma depends on the timing of diagnosis, extent of injury, and associated complications. Early recognition and appropriate surgical intervention are essential to preserve renal function and reduce morbidity. Bilateral ureteral ligation is a rare but severe complication of hysterectomy, often presenting with postoperative anuria or oliguria and requiring urgent urological management. Careful intraoperative identification of the ureters and close monitoring of urine output are critical to prevent and promptly detect ureteral injury.